2009
DOI: 10.1111/j.1939-1676.2009.0275.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Regulating Hormones and Serum Calcium and Magnesium Concentrations in Septic and Critically Ill Foals and their Association with Survival

Abstract: Background: Disorders of calcium regulation are frequently found in humans with critical illness, yet limited information exists in foals with similar conditions including septicemia. The purpose of this study was to determine whether disorders of calcium exist in septic foals, and to determine any association with survival.Hypothesis: Blood concentrations of ionized calcium (Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 59 publications
3
32
0
2
Order By: Relevance
“…Recent studies have documented that dysfunction of various endocrine systems is associated with sepsis and mortality in newborn foals (Hurcombe et al . 2008, 2009; Hart et al . 2009; Barsnick et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have documented that dysfunction of various endocrine systems is associated with sepsis and mortality in newborn foals (Hurcombe et al . 2008, 2009; Hart et al . 2009; Barsnick et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although large‐scale veterinary epidemiological studies are uncommon, a substantial proportion of the critically ill veterinary population is estimated to be septic . The case fatality rate associated with sepsis in a variety of veterinary species is reported to approach 50%, emphasizing the need for a greater understanding of the pathophysiology of sepsis to improve therapeutic practices …”
mentioning
confidence: 99%
“…Low plasma levels of ionized calcium were found in severe colic, gastrointestinal inflammation and induced endotoxemia [24] [25]. In foals, in which sepsis is one of the main causes of death in the neonatal period, hypocalcemia has also been correlated to the severity of disease [26]. On the other hand, Pusterla et al [7] found no significant differences in mRNA expression for IL-1ß, IL-6 and PCT between healthy and septic foals.…”
Section: Discussionmentioning
confidence: 99%